PROPAGACION VEGETATIVA DE Alnus acuminata H.B.K. POR CULTIVO DE TEJIDOS VEGETALES - Hodson de JaramiJlo, Elizabeth; Departamento de Biología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
Severa] types oftissue were cultured, and axilar buds selected as explants for micropropagation of A. acuminata. 'Whole plants were raised from axilar buds isolated from plants 12-18 months old, maintained in greenhouse conditions. As basal media were evaluated: Macro and micronutrients ofMurashige-Skoog (lx; 0.5x), Greshoff & Doy modified by Sommer (Sommer 2), Woody Plant Medium (WPM) and Nitsch with or without the addition of growth regulators: 6 Benziladenine (BA) 0-44mM as citoquinin and Naftalenacetic Acid (NAA) 0-0.107mM as auxin. The best results in foliar and root development were obtained in the MS medium half strength with 0.1 07mM NAA and 44mM BA in the Sommer 2 medium, with addition of0.107mM BA and 22-44mN BA. The developed shoots provenient from these media were micro-propagated using nodal segments grown in MS/2 and Sommer without hormones, in wich